Dampak Induksi Karsinogenesis Glandula Mammae dengan 7, 12-dimetilbenz(?)antrasen terhadap Gambaran Histopatologis Lambung Tikus Sprague Dawley - Tri Budi M, Ranita; Widyarini, Sitarina (Jurnal Veteriner; Vol 11 No 1 (2010))
This experiment was designed to study the impact of mammary carcinogenesis induced by 7,12-dimetilbenz (?) antracene (DMBA) on histopathological features of the gastric in Sprague Dawley rat.Eight female Sprague Dawley (SD) rats, of four week-old, were used in this study. The rats were randomlydivided into 2 groups of four. Group I were treated orally with 20 mg/kg BW of 7,12-dimetilbenz (?)antracene (DMBA) treatment, twice a week for 5 weeks. Group II were used as negative control withoutDMBA treatment. At 5 week after the end DMBA of, the rats of the both groups were sacrificed and thegastric were fixed in 10% buffer formalin. Subsequently, tissue sections were stained with hematoxylinand eosin (H&E) for microscopic examination. The results of the experiment show that oral administrationof DMBA (20 mg/kg BW) twice a week, for 5 weeks result in epithelial hyperplasia of cardia. Hemorrhagicand inflammation reactions are also found on the mucous membrane of fundic. However, macroscopicexamination shows no specific changes of the gastric. Histopathological changes were suspected as a precancer lesion of the gastric due to chronic exposure of DMBA.
Keywords: 7,12-dimetilbenz (?) antracene, mammary carcinogenesis, cardia, fundic